Geophysical significance on Syowa-Iceland conjugate observation in the present stage and near future - Natsuo Sato (National Institute of Polar Research, 1989)
Conjugacy and non-conjugacy of auroral phenomena give us useful information on the acceleration mechanisms for auroral particles and on the generation and propagation mechanism for ULF-VLF waves. However, there have been few conjugate pair of observatories in the northern and southern polar regions. Fortunately, the conjugate point of Syowa Station in Antarctica is located in Iceland. The first conjugate campaign was carried out in 1977,1978,and the second campaign started in 1983 in a more extended scale. This paper summarizes, some significant results for the magnetospheric physics obtained through the conjugate observation, along with a proposal of the future plan.